1993
DOI: 10.1073/pnas.90.14.6577
|View full text |Cite
|
Sign up to set email alerts
|

A mouse homolog of the Escherichia coli recA and Saccharomyces cerevisiae RAD51 genes.

Abstract: Analysis of mitotic and meiotic recombination in mammalian cells has been hampered by the complexity of the reactions involved as well as lack of mutants. Furthermore, none of the genes involved in the process has yet been identified. In budding yeast, Saccharomyces cerevisiae, the RADSI gene is essential along with other genes of the RAD52 epistasis group for mitotic and meiotic recombination and DNA repair. The Rad5l protein is structurally similar toEscherichia coi RecA protein, which is required in homolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(85 citation statements)
references
References 26 publications
(19 reference statements)
2
82
0
1
Order By: Relevance
“…Although partial differentiation of thymocytes and, to a lesser degree, bone marrow cells is promoted by irradiation, the lack of mature peripheral lymphocytes is no doubt due to the inability of radiation to reconstitute the recombinatorial assembly of antigen receptor genes. Thus, it appears that DNA-repair genes, although capable of recombinatorial activity (13)(14)(15)23), do not compensate for the lack of RAG-2 function. Moreover, the genetic alterations that we hypothesize may account for a partial lymphoid maturation and do not appear to act as second-site suppressors to deficiencies in the RAG-2 gene.…”
Section: Resultsmentioning
confidence: 99%
“…Although partial differentiation of thymocytes and, to a lesser degree, bone marrow cells is promoted by irradiation, the lack of mature peripheral lymphocytes is no doubt due to the inability of radiation to reconstitute the recombinatorial assembly of antigen receptor genes. Thus, it appears that DNA-repair genes, although capable of recombinatorial activity (13)(14)(15)23), do not compensate for the lack of RAG-2 function. Moreover, the genetic alterations that we hypothesize may account for a partial lymphoid maturation and do not appear to act as second-site suppressors to deficiencies in the RAG-2 gene.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that synapsis of homozygous chromosomes in the mammalian spermatogenic meiotic process begins at the zygotene stage through chromosome movement and attachment (for reviews, see refs. 21 and 22) and that several factors for SCs, such as RAD51, DMC1, and cohesin, contain functional ATP-binding domains (23)(24)(25). In yeast, it has been demonstrated that mitochondrial respiratory function is essential for meiosis (13)(14)(15) and that mitochondrial dynamics determined by opposing mitochondrial fission and fusion events are important in the meiotic sporulation process (16).…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that GRTH either directly or indirectly influences the apoptosis pathway and the dynamic changes of chromosome events through the regulation of protein expression of relevant genes. It is interesting to note that DNA repair proteins that are necessary for the maintenance of chromosome integrity, such as Rad51 and Dmc1 (14,15), were increased in GRTH Ϫ/Ϫ testis. Rad51 is involved in mitotic and meiotic double-strand DNA break repair and Dmc1 is a germline meiotic-specific gene essential for chromosome synapsis in the first meiotic prophase.…”
Section: Discussionmentioning
confidence: 99%